Efficacy of desmopressin in reducing post-procedural bleeding among chronic kidney disease patients: a systematic review and meta-analysis - Chananchida Sirilertmekasakul; Porpim Jindasakchai; Sudapree Sorasuchart; Tanat Lertussavavivat; Suramath Isaranuwatchai (Frontiers in Medicine, 2026)
Introduction Chronic kidney disease (CKD) is associated with uremic-related platelet dysfunction and a greater risk of perioperative bleeding. Desmopressin (DDAVP) is believed to improve platelet function and is used prophylactically to prevent post-operative bleeding, but with uncertain efficacy. In this research, we evaluated the efficacy of peri-procedural desmopressin administration in reducing bleeding complications in CKD patients. Methods We searched PubMed, Scopus, and Embase up to August 2025 for randomized controlled trials (RCTs) and observational studies involving adult CKD patients undergoing non-surgical procedures who received peri-procedural desmopressin compared to a control group. Outcomes included overall bleeding events, hematoma, hematuria, hematocrit decline, transfusions, and interventions for bleeding control. Safety profile of hyponatremia was also assessed. Results Of 1,744 records, a total of 7,944 participants from 21 studies were included. The meta-analysis showed that desmopressin did not significantly reduce overall bleeding events (OR 0.87, 95% CI 0.57–1.33). Similarly, there was no significant effect on the incidence of hematoma (OR 1.35, 95% CI 0.40–4.53) or hematuria (OR 1.44, 95% CI 0.50–4.12). Subgroup analysis restricted to randomized controlled trials (RCTs) demonstrated a significant reduction in overall bleeding events with desmopressin (OR 0.50, 95% CI 0.29–0.87). Further subgroup analysis by route of administration revealed that the intranasal route was associated with a significant reduction in total bleeding events (OR 0.52, 95% CI 0.32–0.84). Conclusion This study suggests that desmopressin does not significantly reduce post-procedural bleeding in CKD patients. However, subgroup analyses restricted to RCTs, and the intranasal administration route suggest a reduction in bleeding complications. Systematic review registration PROSPERO ID: CRD420251118342, URL: https://www.crd.york.ac.uk/PROSPERO/view/CRD420251118342 .